Association of Fluorescent Protein Pairs and Its Significant Impact on Fluorescence and Energy Transfer. Issue 1 (23rd November 2020) - Pope, Jacob R.; Johnson, Rachel L.; Jamieson, W. David; Worthy, Harley L.; Kailasam, Senthilkumar; Ahmed, Rochelle D.; Taban, Ismail; Auhim, Husam Sabah; Watkins, Daniel W.; Rizkallah, Pierre J.; Castell, Oliver K.; Jones, D. Dafydd
Abstract: Fluorescent proteins (FPs) are commonly used in pairs to monitor dynamic biomolecular events through changes in proximity via distance dependent processes such as Förster resonance energy transfer (FRET). The impact of FP association is assessed by predicting dimerization sites in silico and stabilizing the dimers by bio‐orthogonal covalent linkages. In each tested case dimerization changes inherent fluorescence, including FRET. GFP homodimers demonstrate synergistic behavior with the dimer being brighter than the sum of the monomers. The homodimer structure reveals the chromophores are close with favorable transition dipole alignments and a highly solvated interface. Heterodimerization (GFP with Venus) results in a complex with ≈87% FRET efficiency, significantly below the 99.7% efficiency predicted. A similar efficiency is observed when the wild‐type FPs are fused to a naturally occurring protein–protein interface system. GFP complexation with mCherry results in loss of mCherry fluorescence. Thus, simple assumptions used when monitoring interactions between proteins via FP FRET may not always hold true, especially under conditions whereby the protein–protein interactions promote FP interaction. Abstract : Fluorescent proteins (FP) are an important tool in the life sciences, including monitoring dynamic processes such as protein–protein interactions. Here, it is shown that when FPs associate their core functional parameters can change. Thus, simple assumptions used when monitoring interactions between proteins via FRET may not always hold true, especially under conditions whereby the protein–protein interactions promote FP interaction.